Maternal thyroid hormone status in pre-eclampsia: a tertiary care hospital based study - Deshpande, Sonali; Yelikar, Kanan; Patil, Shreyas; Andurkar, Smita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the study was to study the association between thyroid hormone status with preeclampsia and correlate it with severity of pre-eclampsia. Methods: In this case control study, 200 women attending tertiary care hospital between the study period September 2012 to August 2014 were recruited in the study in which 100 women were cases (diagnosed as preeclampsia) and 100 were taken as control (healthy normotensive women). Assessment of thyroid status of cases and control was done. Association was studied between thyroid hormone status and pre-eclampsia and co-related with severity of preeclampsia. Results: There was a significant association between pre-eclampsia and thyroid hypofunction (overt and sub clinical hypothyroidism) with P-value being 0.0406. Odds-ratio indicates that preeclampsia group have chance of higher TSH (>4.8 mIU/L) by 2.19 times. (95% confidence intervals= 1.0223 –4.6934). The association between severity of pre-eclampsia and thyroid hypofunction (subclinical and overt hypothyroidism) was found to be statistically significant (p= 0.02717). Odds ratio indicates that severe preeclampsia group have 2.87 times more chance of thyroid hypofunction. Conclusions: In the present study a positive association was found between thyroid hypofunction and pre-eclampsia and it was found to be statistically significant. With regards to the results of the present study, “the measurement of serum levels of FT3, FT4 and TSH” can be suggested as a criterion for prediction of pre-eclampsia.